1991
DOI: 10.1111/j.1476-5381.1991.tb12260.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced contractility of the rat stomach during suppression of angiotensin converting enzyme by captopril in vitro

Abstract: 1 Intragastric pressure (IGP) was used as an index, of the effect of serosal application of captopril (SQ 14,225; D-3-mercapto-2-methylpropanoyl-L-proline) on the contractility of rat stomach in vitro. 2 Captopril, at concentrations > 0.3 pm, enhanced the spontaneous gastric motility (GM) in a concentration-dependent manner whereas concentrations <0.3 pM selectively potentiated 4 nm bradykinin (BK)evoked gastric contractions without significantly affecting the spontaneous GM. 3 The kallikrein inhibitor, aproti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They did not receive any medications such as gastrointestinal prokinetic agents, calcium antagonists, tricyclics, narcotics or selective serotonin reuptake inhibitors before or during the test period. Angiotensin‐converting enzyme inhibitor users were also excluded from the present study because this inhibitor has also been reported to influence gastric and esophageal motility 19,20 . Their lifestyle was unchanged during the test period, although there was no alcohol intake within 1 day before every examination.…”
Section: Methodsmentioning
confidence: 99%
“…They did not receive any medications such as gastrointestinal prokinetic agents, calcium antagonists, tricyclics, narcotics or selective serotonin reuptake inhibitors before or during the test period. Angiotensin‐converting enzyme inhibitor users were also excluded from the present study because this inhibitor has also been reported to influence gastric and esophageal motility 19,20 . Their lifestyle was unchanged during the test period, although there was no alcohol intake within 1 day before every examination.…”
Section: Methodsmentioning
confidence: 99%